2009
DOI: 10.1021/jp909785g
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of CoO Porous Nanowire Arrays on Ti Substrate and Their Application as Lithium-Ion Battery Electrodes

Abstract: We report for the first time a facile and direct synthesis of large-scale cobalt monoxide (CoO) porous nanowire arrays (NWAs) with robust mechanical adhesion to flexible conductive substrate (Ti foil) by a two-step method. Significantly raw salt cubic CoO of high quality from the complete pyrolysis of cobalt-hydroxide-carbonate (precursor) is achieved. When serving as lithium-ion battery electrodes in the absence of any ancillary materials (carbon black and binder), the as-obtained well-aligned CoO NWAs, posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 32 publications
7
137
1
Order By: Relevance
“…Xia et al Figs. 4(e) and 4(f). Jin et al 44 also reported a facile and direct synthesis of large-scale cobalt monoxide (CoO) porous nanowire arrays with robust mechanical adhesion to°exible conductive Ti foil through the complete pyrolysis of cobalt-hydroxide-carbonate precursors. In addition, on the basis of a facile hydrothermal route, Wang et al 73 synthesized a series of novel layered hydroxide lanthanum (LHL) crystalline nanowires with hierarchical pores.…”
Section: -5mentioning
confidence: 99%
See 2 more Smart Citations
“…Xia et al Figs. 4(e) and 4(f). Jin et al 44 also reported a facile and direct synthesis of large-scale cobalt monoxide (CoO) porous nanowire arrays with robust mechanical adhesion to°exible conductive Ti foil through the complete pyrolysis of cobalt-hydroxide-carbonate precursors. In addition, on the basis of a facile hydrothermal route, Wang et al 73 synthesized a series of novel layered hydroxide lanthanum (LHL) crystalline nanowires with hierarchical pores.…”
Section: -5mentioning
confidence: 99%
“…43,112 Notably, the nanostructured porous materials with large surface areas will lead to multiple advances in the performance of Li-ion batteries, such as providing shorter path lengths for both electron and Li ion transport, a higher electrode/ electrolyte contact area, a better accommodation of the strain of the Li ion insertion/extraction, etc. Jiang et al 44 examined the electrochemical rate capability of porous CoO nanowires with Li ion insertion and extraction at di®erent rates, and found that this kind of porous CoO nanowires supported on°exible conductive substrate (Ti foil) exhibit good high-rate capability at the rate of 1 C (716 mA g À1 ), 2 C (1432 mA g À1 ), 4 C (2864 mA g À1 ) and 6 C (4296 mA g À1 ), respectively. The as-revealed completely reversible electrochemical properties and unique advantages should originate from the typical porous 1D nanostructured architecture.…”
Section: Rechargeable Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, forming composites with conductive materials such as carbon is a very common and useful method, but often reduces the mass specific capacity [11,12]. So, preparing materials with a special morphologies such as a porous structure [13][14][15][16], nanoarrays [6,17], microspheres [18][19][20][21][22] and some others [23] to enhance the electrochemical performance has attracted much attraction.…”
Section: Introductionmentioning
confidence: 99%
“…Good results at higher C rates have been obtained by combining nanoscale and porosity. In particular, the synthesis of CoO porous nanowire arrays with robust mechanical adhesion to a flexible conductive Ti foil exhibit good high-rate capability at a rate of 1C (716 mA g À1 ), 2C (1432 mA g À1 ), 4C (2864 mA g À1 ), and 6C (4296 mA g À1 ), respectively [488]. Hierarchically self-assembled mesoporous CoO nanodisks synthesized by the reaction of cobalt acetate tetrahydrate with hydrazine hydrate in solution followed by heat treatment in an inert atmosphere delivered a capacity of 1118.6 mAh g À1 after 50 discharge-charge cycles at 200 mA g À1 and excellent cycling performance: 633.5 mAh g À1 after 400 discharge-charge cycles at 800 mA g À1 [489].…”
mentioning
confidence: 99%